Pengaruh Kepuasan Kerja dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Universitas Muhammadiyah Palangkaraya - Iin Nurbudiyani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This research aims at knowing: (1) influence of working satisfaction on work spirit lecturer and employee University of Muhammadiyah Palangkaraya, (2) influence of fieldwork on work spirit lecturer and employee University of Muhammadiyah Palangkaraya, (3) influence of working satisfaction and fieldwork collectively on work spirit lecturer and employee University of Muhammadiyah Palangkaraya. Research is done in the official University of Muhammadiyah Palangkaraya RTA Milono Street Km 1,5 Palangka Raya Central Kalimantan. Variables will be researched: (1) Free Variable (Working Satisfaction and Fieldwork), and (2) Bound Variable (Work Spirit). The population is all lecturers and employees in the official University of Muhammadiyah Palangkaraya which amount more or less 100 people in this research. 100 populations were made as a group based on their work section, they are 65 lecturers and 35 section of personnel. Data collection uses a questionnaire and documentation. This data is supplied in form of frequency distribution table, then to identify inclination each free variable and bound variable uses ideal average score (M) and ideal standard deviation (SD) then it is determined classification. Research result was: (1) Working satisfaction of lecturer and employee on the official University of Muhammadiyah Palangkaraya had enough inclination, (2) There were significant influence of working satisfaction on work spirit, (3) There was significant influence of fieldwork on spirit work, (4) There were significant influence on working satisfaction and fieldwork collectively on working satisfaction.